Antibacterial Effects of Basil (Ocimum sanctum) Leaf Extract in Combination with Meropenem against Extended Spectrum Beta-Lactamase (ESBL) Producing Klebsiella pneumoniae - Lifindra, Billy Yanssen; Wiqoyah, Nurul; Indiastuti, Danti Nur (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2024)
Highlights: Ocimum sanctum leaf extract does not significantly increase its antibacterial effects when combined with meropenem against ESBL-producing K. pneumoniae. Ocimum sanctum leaf extract has different antibacterial effects depending on geological and environmental factors.   Abstract Introduction: Antibiotic usage for bacterial infections causes antibiotic resistance in bacteria. One is extended-spectrum beta-lactamase (ESBL), which produces Klebsiella pneumoniae, a pathogen responsible for increased antibiotic resistance. Basil (Ocimum sanctum) is a candidate for combination therapy. It has been proven to have antibacterial effects. However, its combination with antibiotics is rarely researched. This study evaluated the antibacterial effects of O. sanctum leaf extract and meropenem combination against ESBL-producing K. pneumoniae. Methods: This study used the disk diffusion method. The extract was tested for each experiment at 6%, 4%, 2%, 1%, and 0.5% concentration. The research was divided into two experiments to evaluate the antibacterial effects of O. sanctum leaf extract (n=18) and its combination with meropenem against ESBL-producing K. pneumoniae (n=18). The data was analyzed using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0 for Windows. A probability p<0.050 was considered significant. Results: The first experiment showed that the extract had the largest antibacterial effect at 0.5% concentration (n=18, p=0.007). Meanwhile, the second experiment showed that the combination of the extract and meropenem did not have significant antibacterial effects (n=18, p=0.597). Conclusion: Ocimum sanctum leaf extract has viable antibacterial effects, but its combination with Meropenem does not significantly improve its antibacterial effects against Extended Spectrum Beta-Lactamase (ESBL) producing K. pneumoniae.